Principles and practice of travel medicine - Zuckerman, Jane N. ([Chichester] : Wiley-Blackwell, 2013)
This second edition of Principles and Practice of Travel Medicine has been extensively updated to provide a comprehensive description of travel medicine and is an invaluable reference resource to support the clinical practice of travel medicine. This new edition covers the many recent advances in the field, including the development of new and combined vaccines; malaria prophylaxis; emerging new infections; new hazards resulting from travel to long haul destinations; health tourism; and population movements. The chapter on vaccine-preventable diseases includes new developments.
Section I: Travel Medicine. Trends in Travel / Thomas L Treadwell -- Tourism, Aviation and the Impact on Travel Medicine / Anne Graham -- Epidemiology of Health Risks and Travel / Hans D Nothdurft, Eric Caumes -- Fitness to Travel / Dominique Tessier -- Management of a Travel Clinic / Abinash Virk, Elaine C Jong -- Section II: Infectious Diseases and Travel. Epidemiology and Surveillance of Travel-Related Diseases / Tomas Jelinek -- Virus Infections in Travellers / Arie J Zuckerman -- Bacterial Infections in Travellers / Ann L N Chapman, Christopher J Ellis -- Vector-Borne Parasitic Diseases / Emma C Wall, Peter L Chiodini -- Malaria and Travellers / David J Bell, David G Lalloo -- Emerging and Re-Emerging Infectious Diseases / Francisco G Santos O'Connor -- Section III: Prevention and Management of Travel-Related Diseases. Skin Tropical Infections and Dermatology in Travellers / Francisco Vega-López, Sara Ritchie -- Travellers' Diarrhoea / Charles D Ericsson -- Vaccine-Preventable Disease / Jay Halbert, Phyllis Kozarsky, Jane Chiodini, Nicholas Zwar, Gary Brunette, Jane N Zuckerman -- Returned Travellers / Nicholas J Beeching, Tom E Fletcher, Limin Wijaya -- Section IV: Hazards of Air and Sea Travel. Aviation Medicine / Michael Bagshaw -- Aviation Psychology / Robert Bor, Carina Eriksen, Margaret Oakes, Philip Baum -- Expedition and Extreme Environmental Medicine / Sean Hudson, Andrew Luks, Piers Carter, Luanne Freer, Caroline Knox, Chris Imray, Lesley Thomson -- Travel Health at Sea: Cruise Ship Medicine / Robert E Wheeler -- Section V: Environmental Hazards of Travel. Travel-Related Injury / Robert Grenfell -- International Assistance and Repatriation / Alex T Dewhurst, John C Goldstone -- Venomous Bites and Stings / R David G Theakston, David G Lalloo -- Ophthalmic Conditions in Travellers / Clare Davey, James Tee -- Section VI: Practical Issues for Travellers. Travelling with Children (Including International Adoption Issues) / Philip R Fischer, Andrea P Summer -- Women's Health and Travel / I Dale Carroll, Susan Anderson -- The Immunocompromised Traveller / Robert J Ligthelm, Pieter-paul A M van Thiel -- High-Risk Travellers / Kathryn N Suh, Anne E McCarthy, Maria D Mileno, Jay S Keystone -- Aid Workers, Expatriates and Travel / Kenneth L Gamble, Deborah M Hawker, Ted Lankester, Jay S Keystone -- The Health of Migrants and Refugees / Louis Loutan, Sophie Durieux-Paillard, Ariel Eytan -- Visiting Friends and Relatives / Delane Shingadia -- Travel Medicine, Ethics and Health Tourism / Deborah Bowman, Richard Dawood -- Medico-Legal Issues in Travel Medicine / Jennifer G Baine, Paul S Auerbach -- Travellers' Safety and Security / Peter A Leggat, Jeff Wilks -- The International Athlete: Travelling Healthy to Global Sporting Events / Travis W Heggie, Sarah Borwein, Marc T M Shaw -- Space Tourism -- The Future in Travel Health? / Kevin J Fong, Mark H Wilson.
Includes index.
ReferencesSection II: Infectious diseases and travel; Chapter 6: Epidemiology and surveillance of travel-related diseases; Introduction; Systematic observations; Malaria; Dengue fever; Risk estimates; Detection of sentinel events; Falciparum malaria in the Dominican Republic; African trypanosomiasis from Tanzania; Falciparum malaria in illegal Chinese immigrants; Falciparum malaria in travellers to Gambia; Conclusions; References; Chapter 7: Virus infections in travellers; Viral hepatitis; Introduction and definitions; Hepatitis A; Introduction and definitions; Nature of the virus.
Print version record.
Keywords: Travel -- Health aspects; Communicable Disease Control; Travel; Primary Prevention; HEALTH & FITNESS -- Diseases -- Contagious; MEDICAL -- Infectious Diseases; Travel -- Health aspects; Electronic books